Advances in Green Bromination: Emerging Eco-Friendly Reagents and Methodologies - Magar, Vidya Kishanrao; Khavane, Karna Bhagwanrao; Shaikh, Sameena Ibrahim; Sangule, Dipali Vishwanath; Shelke, Santosh Dattatraya (Indian Journal of Pharmaceutical Education and Research, 2026)
In light of the growing emphasis on sustainable practices in modern chemistry, this review critically examines recent advancements in environmentally benign methods for the bromination of organic compounds. Bromination, a transformation of significant synthetic and industrial relevance, has traditionally relied on harsh reagents and conditions that raise environmental and safety concerns. This review focuses on "green" strategies developed for the selective introduction of bromine atoms into organic molecules, encompassing both direct bromination and oxidative bromination methodologies. Emphasis is placed on approaches that minimize hazardous waste, utilize safer brominating agents, and operate under milder reaction conditions. Particular attention is given to catalytic systems, solvent-free protocols, aqueous media, and the use of renewable feedstock’s. Each method is evaluated not only for its synthetic efficiency and selectivity but also through the lens of sustainability metrics, including atom economy, energy efficiency, and environmental impact. By compiling and analyzing recent literature, this review aims to provide a comprehensive understanding of current progress and remaining challenges in the field of green bromination chemistry.
Keywords: Green Bromination; Eco-friendly Reagents; Sustainable Chemistry; Oxidative; bromination; Selective halogenation; Catalytic bromination